2019
DOI: 10.1002/ajpa.23899
|View full text |Cite
|
Sign up to set email alerts
|

Morphological integration affects the evolution of midline cranial base, lateral basicranium, and face across primates

Abstract: Objectives: The basicranium and face are two integrated bony structures displaying great morphological diversity across primates. Previous studies in hominids determined that the basicranium is composed of two independent modules: the midline basicranium, mostly influenced by brain size, and the lateral basicranium, predominantly associated with facial shape. To better assess how morphological integration impacts the evolution of primate cranial shape diversity, we test to determine whether the relationships f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 87 publications
1
12
1
Order By: Relevance
“…However, the results in the present study only partially corresponded to these previous studies, as the magnitude of integration in the chondrocranium/face complex was significantly higher than for the skull as a whole in juvenile groups (p < .001), but not in adults (U = 500,530, p = .9675; Table S1). One possible reason for the discrepancy between the present and previous investigations is that some studies were performed on endocranial morphology of the basicranium/face complex (Gkantidis & Halazonetis, 2011;Lieberman, Pearson, et al, 2000;Lieberman, Ross, et al, 2000;Neaux, 2017;Neaux et al, 2018;Neaux, Guy, Gilissen, Coudyzer, & Ducrocq, 2013;Neaux, Wroe, Ledogar, Heins Ledogar, & Sansalone, 2019;Scott et al, 2018). Nevertheless, our results likely indicate that the chondrocranium/face complex is not as tightly integrated in adults as it is in juveniles.…”
Section: Chondrocranium/face Complexcontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the results in the present study only partially corresponded to these previous studies, as the magnitude of integration in the chondrocranium/face complex was significantly higher than for the skull as a whole in juvenile groups (p < .001), but not in adults (U = 500,530, p = .9675; Table S1). One possible reason for the discrepancy between the present and previous investigations is that some studies were performed on endocranial morphology of the basicranium/face complex (Gkantidis & Halazonetis, 2011;Lieberman, Pearson, et al, 2000;Lieberman, Ross, et al, 2000;Neaux, 2017;Neaux et al, 2018;Neaux, Guy, Gilissen, Coudyzer, & Ducrocq, 2013;Neaux, Wroe, Ledogar, Heins Ledogar, & Sansalone, 2019;Scott et al, 2018). Nevertheless, our results likely indicate that the chondrocranium/face complex is not as tightly integrated in adults as it is in juveniles.…”
Section: Chondrocranium/face Complexcontrasting
confidence: 99%
“…However, our results for adults differ from those of Shirai and Marroig (2010), as the magnitude of integration in the chondrocranium was similar in magnitude to the vault/chondrocranium complex, and higher in magnitude than the chondrocranium/face complex (Figure 3). These results indicate that the chondrocranium module of juveniles (but not adults) requires a lower magnitude of integration for more coordination with adjacent soft tissue (i.e., brain) or other cranial regions in early ontogenetic stages because the chondrocranium serves as a platform for development and growth of the brain (Lieberman, 2011; Neaux et al, 2018; Neaux et al, 2019; Neubauer et al, 2009). For instance, Neaux et al (2019) reported that there was significant morphological integration between the midline basicranium and endocranial volume across primates, which may indicate a significant effect of brain size on the shape of midline morphology in the cranial base.…”
Section: Discussionmentioning
confidence: 99%
“…The exact ontogenetic mechanism by which the observed cranial base changes may lead to shape change across the entire cranium in Longshanks remains to be elucidated. There is extensive evidence for strong phenotypic covariation among cranial traits (i.e., morphological integration) causing indirect change throughout the cranium (Bookstein et al, 2003;Goswami, 2006;Goswami et al, 2012;Singh et al, 2012;Bastir and Rosas, 2016;Neaux, 2016;Neaux et al, 2019). For example, direct basicranium perturbations by genetic mutations in mice generated predictable shape changes throughout the cranium (Parsons et al, 2015).…”
Section: Developmental Correlates Of Shape Changementioning
confidence: 99%
“…Based on a similar criterion [32], the latter has been also divided in two additional regions: i.e. the basicranium with endochondral ossification from a cartilaginous mesodermic precursor (chondrocranium) [3, [33][34][35][36][37], and the calvaria whose bones derive from the desmocranium, which has an intramembranous ossification from paraxial mesoderm and neural crests cells [38]. In fact, different studies have shown that the patterns of covariation and correlation between different parts of the cranium are partially independent, thus suggesting that they behave as partially independent units [15,[39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%